Out of Operating Room Anesthesia : A Comprehensive Review - Goudra, Basavana G.; Singh, Preet Mohinder (Springer International Publishing : Imprint: Springer, 2017)
This book covers all aspects of out of operating room anesthesia and deep sedation practice. The practical aspects of anesthesia are emphasized, with particular stress on management of unanticipated adverse events. A concise, yet comprehensive description of relevant basic sciences is also included. Although the contributors are predominantly North American, essential elements of out of OR practice in countries other than the USA are incorporated. Out of Operating Room Anesthesia: A Comprehensive Review, is primarily aimed at all anesthesia providers: anesthesiologists, nurse anesthetists and residents. Specific chapters such as dental anesthesia, anesthesia for ER procedures and sedation for cosmetic procedures are a useful reference guide to physicians exposed to brief training in anesthesia during their non-anesthesia residency program.
Keywords: Medicine.; Anesthesiology.; elektronické knihy; electronic books